2014
DOI: 10.3389/fnsys.2014.00075
|View full text |Cite
|
Sign up to set email alerts
|

Partial sleep in the context of augmentation of brain function

Abstract: Inability to solve complex problems or errors in decision making is often attributed to poor brain processing, and raises the issue of brain augmentation. Investigation of neuronal activity in the cerebral cortex in the sleep-wake cycle offers insights into the mechanisms underlying the reduction in mental abilities for complex problem solving. Some cortical areas may transit into a sleep state while an organism is still awake. Such local sleep would reduce behavioral ability in the tasks for which the sleepin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 110 publications
(127 reference statements)
0
14
0
1
Order By: Relevance
“…It may also be worth noting that after a waking experience brain activity keeps on acquiring new percepts in addition to processing waking percepts. Notably during sleep brain cortical regions are not exclusively involved in processing environmental information; they are also busy receiving and processing stimuli largely derived from the gastrointestinal tract (Pigarev, 1994 ; Pigarev et al, 2013 ; Pigarev and Pigarev, 2014 ). It follows that heterogeneous synaptic populations analyzed by random methods may include synaptic elements that are not related to waking memories.…”
Section: Comparing Shy With Shmentioning
confidence: 99%
“…It may also be worth noting that after a waking experience brain activity keeps on acquiring new percepts in addition to processing waking percepts. Notably during sleep brain cortical regions are not exclusively involved in processing environmental information; they are also busy receiving and processing stimuli largely derived from the gastrointestinal tract (Pigarev, 1994 ; Pigarev et al, 2013 ; Pigarev and Pigarev, 2014 ). It follows that heterogeneous synaptic populations analyzed by random methods may include synaptic elements that are not related to waking memories.…”
Section: Comparing Shy With Shmentioning
confidence: 99%
“…This opinion may meet disagreement based on a doubt concerning the increased involvement of the cerebral cortex in the processing of visceral information during sleep. Our view is based on electrophysiological experiments performed in rabbits, cats, and monkeys (see for review, e.g., Pigarev, 2014;Pigarev and Pigareva, 2014). However, results of these studies are not widely known yet, most likely because their subject, being located between three very different disciplines-classical sensory physiology, physiology of the visceral systems and sleep research, usually slips attention of the corresponding three groups of researchers.…”
mentioning
confidence: 99%
“…It is known that local or partial sleep also starts developing from these cortical areas (Pigarev et al, 1997). According to the visceral theory of sleep (Pigarev and Pigareva, 2014) development of the local sleep in limited parts of the cerebral cortex indicates the onset of visceral information transfer to those cortical areas while behaviorally this state correspond to wakefulness or drowsiness. In addition, it was reported that epileptic attacks often happen during developing drowsiness (Mirzoev et al, 2012).…”
mentioning
confidence: 99%
“…For example, it is a well known fact that in conditions when it is necessary to remain awake in spite of high natural sleep pressure a local sleep develops in high order cortical areas. At that simple behavioral activities, which do not need engagement of the highest cortical resources, are still maintained even when part of the brain is sleeping [19]. It is evident that to ensure such a brain plasticity in information processing more complex gating system is needed than shown in Fig.…”
Section: The Visceral Theory Of Sleepmentioning
confidence: 99%